2009
DOI: 10.1093/annonc/mdn646
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to adjuvant endocrine therapy in postmenopausal women with breast cancer

Abstract: An important goal of any therapeutic intervention is to achieve comparable efficacy in routine clinical practice to that demonstrated in randomised clinical trials. However, a similar magnitude of adherence will be necessary in routine clinical practice to assure comparable clinical effects. Our results further support the data on suboptimal adherence of women with breast cancer on adjuvant TAM treatment. Here, we evaluated for the first time the patient reported and real-world adherence on adjuvant ANA and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
191
2
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(203 citation statements)
references
References 20 publications
3
191
2
7
Order By: Relevance
“…While several studies have reported treatment discontinuation rates of patients starting with AIs after 1 year of follow-up [7,26,27], long-term observational studies are needed in the future to determine treatment continuation and switching patterns during 5 years of follow-up of patients starting on AIs.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have reported treatment discontinuation rates of patients starting with AIs after 1 year of follow-up [7,26,27], long-term observational studies are needed in the future to determine treatment continuation and switching patterns during 5 years of follow-up of patients starting on AIs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a study of tamoxifen adherence based on electronic monitoring, pill counts, and patient self-reporting, adherence was significantly overestimated in self-reports ( p = 0.008) 8 . In another recent study, self-reported adherence was 100%, which did not correlate with prescription refill data 9 . Consequently, studies that use self-reported adherence data (such as most clinical trials) may over-report medication adherence.…”
Section: Introductionmentioning
confidence: 86%
“…In a recent comparison of 50 women on tamoxifen and an equal number on anastrozole, 80% on tamoxifen were adherent compared with 69% on anastrozole, as measured by dispensed prescriptions over a median duration of 13.6 months for tamoxifen and 16.6 months for anastrozole 9 . Patients on anastrozole were significantly older (mean: 72 years vs. 65 years for those on tamoxifen).…”
Section: Non-trial Settingsmentioning
confidence: 99%
“…Among the most prominent is the use of endocrine therapy in hormone receptor-positive patients, who compose the majority of breast cancer survivors. Although the problem of early discontinuation and nonadherence to endocrine therapy has been documented in a variety of patient populations [83][84][85][86][87][88][89][90][91][92][93], little is known about differences in endocrine therapy adherence among women of different races. Studies have shown conflicting relationships between race and endocrine therapy utilization among hormone receptor-positive subtypes [85,87,88,94].…”
Section: Treatment Differencesmentioning
confidence: 99%